PENGARUH INTERVENSI MINDFULNESS TERHADAP TINGKAT KECEMASAN IBU HAMIL: LITERATUR REVIEW - Sugarni, Mika; Milawati Ramli, Ramlah; Lestari Salim, Ika; Wulandari, Bety Anisa; Rohmawati, Wahidah; Wulan, Wulan (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2025)
Anxiety in pregnant women is a mental health problem that has a significant impact on maternal and foetal well-being. Mindfulness-based interventions have been widely investigated as a potential non-pharmacological approach to reduce anxiety during pregnancy. This study aims to review the current literature (2020-2024) on the effectiveness of mindfulness interventions on anxiety in pregnant women. Through a search of PubMed, Scopus, and ScienceDirect databases, using the combined keywords: ‘mindfulness’, ‘pregnancy’, “anxiety”, ‘maternal mental health’, and ‘mindfulness intervention for pregnant women’, as well as Boolean operators such as AND and OR. A total of 34 articles met the inclusion criteria and were analysed using thematic analysis method. The results of the review showed that most of the studies reported a significant reduction in anxiety levels in the group of pregnant women who participated in the mindfulness intervention. This intervention was considered effective, easy to implement, and without side effects. These findings support the use of mindfulness as part of antenatal care services to improve the mental health of pregnant women.